Optimization of Stock Portfolio of Value30 Index and Growth30 Index Using The Markowitz Model and Sharpe Model - Kalebos, Adrian H; Rudianto, Dudi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2022)
This study aims to determine the results of optimizing stock portfolios on the Value30 and Growth30 indexes on the Indonesia Stock Exchange based on the Markowitz Model and Sharpe Model. There are seven stocks that are consistently listed on the Value30 index selected with the code ADRO, BJBR, ELSA, ITMG, PTBA, PTPP, UNTR and seven stocks that are consistently listed on the Growth30 index selected with the code ACES, BBCA, BBRI, CPIN, ERAA, TBIG , TOWR. The data is taken from the period January 2015 to December 2021. Using the Markowitz model on the Value30 index stock, from the comparison of the yields a return and standard deviation, the Coefficient of Variation/CV value is 7.426, and for the Growth30 index stock, the CV value is 3.279. Meanwhile, by using the Sharpe model on the Value30 index stock, a CV value of 4.937 was obtained, while the Growth30 index stock obtained a CV value of 3.169 This study concludes that the use of the Sharpe Model provides more optimal results than the Markowitz Model in portfolio formation both on the Value30 index stock and the Growth30 index with the proportion of funds being dominated by ADRO stocks for the Value30 index and BBCA stocks for the Growth30 index.